IMPLEMENTASI KEBIJAKAN RETRIBUSI SAMPAH DI KELURAHAN GADANG KECAMATAN SUKUN KOTA MALANG - Kamalludin Kamalludin (REFORMASI, 2013)
This study aims to determine the various factors that influence success and failure of implementation of the Regional Regulation of Malang City Number 5 of 2001 on the Regional Municipality Amendment II Malang No. TK. 6 Year 1989 On Implementation of Hygiene Malang mainly levy collection and remittance of cleanliness in the Village of Tower District Breadfruit Malang. Factors that influence the degree of success and failure of the Implementation Regulation, the author refers to the State Policy Theory and the Theory of Policy Implementation mainly put forward by George Edward III. From the results of a qualitative descriptive analysis can be revealed that the factors that influence success and failure of policy implementation can be seen from the communication variables (include: clarity of factors and mechanisms to deliver information delivery process orders and directives in user charges for collection of cleanliness). Variable resources (including: the adequacy of the implementing authorities, the carrying capacity of the facility and the adequacy of funds), the variable attitude of the conduct (including: the level of understanding and implementing compliance) and variable structure of the bureaucracy (including decentralization of authority, hierarchy coherence and clarity as well as the implementing agency and detailed formal rules). The results of field observations show no consistency purposes, so the intent and purpose of the regulation has not reached the maximum. This is demonstrated by the amount of waste that can not be taken away and reluctance to pay a compulsory levy of user charges, but the socialization of the area is good regulation. Conclusions obtained, namely the implementation of Regulation No.5 of 2001 have failed. This was caused by the persistence of the quasi-compliance of the implementing authorities, lack of resources and lack of authority given to officers. Therefore the authors recommended that governments revise regulations Malang area and provide sufficient authority to the executive officers and increase resources.